Juridicial Review Of Good Looking Requirements On Job Vacancy Information - Diplomat King Agape Sembiring; Tomy Michael (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2022)
The purpose of this study was to determine how the rules of law and how legal certainly regarding the terms of good looking at job vacancy information, which is by methodempirical juridical research concluded : 1. that by including good looking requirements in employee vacancy information is a form of discrimination and violates the rules of law regarding the requirements that may be included in job vacancy information according to Article 15 Paragraph (3) of the Minister of manpower Regulation Number 39 of 2016 concerning the placement of Labor and Law Number 39 of 1999 concerning human rights. 2. employees who are hired should be seen from the abilities and competencies that match the demands of the job not from their physical appearance. 3. if a company requires good looking requirements, then these requirements do not need to be included in job vacancy information, because good looking has a subjective nature.